The Amadori rearrangement as glycoconjugation method: Synthesis of non-natural C-glycosyl type glycoconjugates - Gallas, Katharina; Pototschnig, Gerit; Adanitsch, Florian; Stütz, Arnold E.; Wrodnigg, Tanja M. (Beilstein Journal of Organic Chemistry, 2012)
The Amadori rearrangement was investigated as a potential method for the conjugation of carbohydrate moieties to suitable amino components. Starting from selected aldoheptoses, which are readily available by means of the Kiliani–Fischer C-elongation reaction of the corresponding aldohexoses, glycoconjugates presenting D-gluco, D-manno and D-galacto as well as GlcNAc motifs have been synthesised. Following this strategy, non-natural C-glycosyl type glycoconjugates, which can be utilised as building blocks for the composition of larger molecular constructions, are available by a very short synthetic approach.
Keywords: Amadori rearrangement; C-glycosyl type glycoconjugates; carbohydrate elongation; non-natural carbohydrate conjugates